The Effect of Family Function and Conflict on Family Subjective Well-being with Migrant Husband - Herawati, Tin; Endah, Nafi Yuliana (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
Poverty, limited employment opportunities, and low rate of labor wage cause couples undergo long distance married because the husband has to work far from the house. This gives impact to family subjective well-being so that the family need to role a family function in order to minimize conflicts. This research aimed to analyze the effect of family function and conflict on family subjective well-being with migrant husband. There were 60 samples in this research which consisted of family with migrant husband teenager children (12-17 years old) in Banyuresmi village, Garut. The wife was the respondent of this research. The sampling technique used here was nonprobability sampling method with form purposive sampling. The data were collected by interviewing the respondents using a questionnaire. The results showed that most of the samples were categorized into families which had good family function, moderate family conflict, and moderate family subjective well-being. Family function affect significantly positive to family subjective well-being. Parental-teenagers conflict affect significantly negative to family subjective well-being.